Dissemination and Adoption of Bundled Agronomic Practices in Vietnam, Benin, Togo, Nigeria and Brazil - CGIAR Research Program on Rice (2020)
In the previous two decades, members of the RICE CRP, including created and disseminated regionally-designed and locally-appropriate portfolios of agronomic practices in collaboration with local partners. we find that previously published levels of dissemination and adoption tend to be inflated. However, this does not mean that the adoption of these technologies is limited. We document reliable sources of data on adoption for each technology and, where appropriate, use these data to estimate adoption rates in the regions of interest.